PENGEMBANGAN DESAIN ANTARMUKA SIMPER DI BADAN METEOROLOGI DAN KLIMATOLOGI MEDAN BERBASIS WEB - Samsudin, Samsudin; Putra, Muklas Adi; Ginting, Natal; Haloho, Melanthon Pardamean (JURSIMA, 2023)
The large amount of work piling up at BMKG Region 1 Medan means there is no time to carry out maintenance on the SIMPER website. So the SIMPER website was handed over to the author to update the icons, tool data and station data. Maintenance is carried out during the internship period or ± 1 month, so that the SIMPER website can provide information on stations that are active or have repaired measuring equipment. In making icons, the author designs icons using the Android application, namely Pixellab. In this research the author used the System Development Life Cycle (SDLC) development method. The aim of this research is to change the tool icon on the SIMPER web so that the icon display is better than before and it is easy to indicate whether it is active or not with the shape of the space and with images related to the previous icon and the aim of updating the tool data is to indicate on the initial appearance of the web SIMPER that the station is active or inactive (has not updated data).